Concrete Paving Block Using Bagasse Ash and Calcium Carbide Residue with Sand and Calcite Residue as Fine Aggregate - Somna, Rattapon; Khamput, Prachoom; somna, kiatsuda (RMUTL Engineering Journal, 2025)
This research focuses on the development of concrete paving blocks using bagasse ash and calcium carbide residue as binders, with sand and calcite residue as fine aggregates. Bagasse ash is a by-product from biomass power plants, calcium carbide residue is a waste material from acetylene gas production, and calcite residue is obtained from limestone mining. The concrete paving blocks were produced using a binder-to-aggregate ratio of 1:3 by weight and a water-to-binder ratio from 0.45 to 0.63. The ratios of bagasse ash to calcium carbide residue used were 90:10, 70:30, and 50:50 by weight. Additionally, ordinary Portland cement was incorporated at 10%, 20%, and 80% by weight of the binder for the 70:30 mixture. The effects of using calcite residue as a fine aggregate replacement for sand were investigated using sand-to-calcite residue ratios of 100:0, 75:25, 50:50, 25:75, and 0:100 by weight, based on a binder ratio of bagasse ash to calcium carbide residue of 70:30. The concrete paving blocks were hand-formed and tested for compressive strength at the ages of 3, 7, 14, and 28 days, and for water absorption at 28 days. The results indicate that the 70:30 mixture of bagasse ash to calcium carbide residue with 80% cement replacement achieved the highest compressive strength and lowest water absorption. When calcite residue was used as the fine aggregate, the 0:100 sand-to-calcite residue ratio provided the highest compressive strength among the replacement levels, although it remained lower than when using sand alone. Although the compressive strength of these concrete paving blocks did not meet the standard requirements of TIS 827-2565, they still exceeded 17 MPa, making them suitable for non-load-bearing applications. This study demonstrates a practical approach for utilizing industrial byproducts, reducing cement consumption, lowering production costs, and promoting environmental waste management.